Functional Deficits and Structural Changes Associated With the Visual Attention Network During Resting State in Adult Strabismic and Anisometropic Amblyopes - Wang, Hao; Liang, Minglong; Crewther, Sheila G.; Yin, Zhengqin; Wang, Jian; Crewther, David P.; Yu, Tao (Frontiers in Human Neuroscience, 2022)
Our previous study has shown impaired BOLD/FMRI activation of the visual attention network in strabismic amblyopia (SA). However there has been no comparison of resting state fMRI activation and functional connectivity in brain regions of interest (ROIs) along the visual attention network including visual cortex (V1), intra parietal sulcus (IPS), and frontal eye fields (FEF) during closed eye resting across the SA (n=20, 13LE), or anisometropic amblyopes AA (n=20, 13LE) groups. Hence, we compared, grey matter volume (GMV), amplitude of low frequency fluctuations (ALFF), regional homogeneity (ReHo) and functional connectivity (FC) in the left and right hemisphere ROIs of the visual attention network in SA, AA, and healthy controls (HC) (n=21). Correlation analyses of corrected visual acuity (cVA) of amblyopic eye and MRI results were also performed and showed that the LogMAR cVA of the amblyopic eye positively correlated with right zALFF and zReHo FEF of SA and right IPS of AA only. GMV of both left and right hemisphere V1 areas was significantly greater but ALFF was significantly lower for SA compared to AA and HC groups. zALFF and zReHo analyses in the AA and SA groups indicated significantly higher activation than that in the HC group in the right FEF and IPS but lower than that in the HC group in the left FEF, and only the SA group showed lower activation in both V1 areas than the HC group. FC values of the right FEF–left V1, right FEF–right V1, and right FEF–right IPS pathways in the SA and AA groups were also significantly higher than those in the HC group whereas all other functional connectivity values were nonsignificant. Thus, this study indicates that even during resting-state the visual attention network function is impaired in SA and AA participants with only right hemisphere FEF showing significant activation in SA and IPS in AA suggesting that the slower saccade activation times characteristic of amblyopic eyes lead to the dominant eye controlling activation of the visual attention network.